2018
DOI: 10.3390/app8122596
|View full text |Cite
|
Sign up to set email alerts
|

Plenty of Room at the Bottom: Nanotechnology as Solution to an Old Issue in Enhanced Oil Recovery

Abstract: During the past half-century, the prefix "nano" attached to several words, such as "technology", "motors", "device", and so on has denoted cutting-edge research fields and topics at the forefront of classical scientific disciplines. Possible application fields have been frequently evoked, even if real-life examples are still difficult to find. The present review analyzes how nanotechnology is utilized in enhanced oil recovery (EOR) processes so as to increase the efficiency of mature oilfields. Nanotechnology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 162 publications
(272 reference statements)
0
30
0
1
Order By: Relevance
“…Among the methods of enhanced oil recovery, there is a wide range of processes that take advantage of the thermal properties of steam to generate the decomposition of heavy molecules through gasification, methanation, steam reforming, hydrogenation, aquathermolysis, and water-gas shift reactions [47]. The aquathermolysis reactions begin with the cleavage of the bonds C-S present in the molecular structure of the n-C 7 asphaltenes, generating the production of H 2 S, because C-S bonds are the bonds with smaller energy of dissociation [126]. The reaction mechanism is shown below…”
Section: Influence Of Nanoparticles In Steam Injection Processesmentioning
confidence: 99%
“…Among the methods of enhanced oil recovery, there is a wide range of processes that take advantage of the thermal properties of steam to generate the decomposition of heavy molecules through gasification, methanation, steam reforming, hydrogenation, aquathermolysis, and water-gas shift reactions [47]. The aquathermolysis reactions begin with the cleavage of the bonds C-S present in the molecular structure of the n-C 7 asphaltenes, generating the production of H 2 S, because C-S bonds are the bonds with smaller energy of dissociation [126]. The reaction mechanism is shown below…”
Section: Influence Of Nanoparticles In Steam Injection Processesmentioning
confidence: 99%
“…However, this technology can be considered relatively new, and large field applications have not been documented in the literature [15]. Druetta et al reported a comprehensive review of the application of nanotechnology in EOR [16]. However, this research also recognized that there are some limitations of the technology that must be addressed.…”
Section: Css With Nanoparticlesmentioning
confidence: 99%
“…The use of nanoparticles to generate physical and chemical changes due to their interaction with heavy crude oils has been widely proposed. Heat transfer improvement and viscosity reduction (e.g., breakage of C-S bonds and hydrogenation of unsaturated bonds) are among the proposed mechanisms during the interaction of crude oil and nanoparticles [16][17][18][19][20][21][22][23].…”
Section: Css With Nanoparticlesmentioning
confidence: 99%
“…The properties of foam fluids related to oil recovery can be modified to better adapt to the geological conditions; this is usually accomplished by changing the composition, preparation method, and/or preparation conditions of the foam system [4,5]. Most improvements have focused on improving the stability, salt resistance, temperature resistance and oil resistance of the foam [6,7]. Bubbles in the foam fluid can lose their shape over the course of the flooding process, as the foam system is in a state of foaming-flowing-defoaming dynamic equilibrium in the porous media encountered.…”
Section: Introductionmentioning
confidence: 99%